Henry Rider Haggard’s Posthumanist Eco-consciousness - Sinan AKILLI (E-REA)
In this essay I argue that the late Victorian and early Edwardian novelist Henry Rider Haggard had a distinct eco-consciousness that was reminiscent of twenty-first century posthumanist philosophies as early as the 1880’s. Writing his “imperial romances” in the wake of the beginnings of what is now called the Anthropocene age, Haggard observed and understood the changing relationships between the human society and the more-than-human world in this historical period. In a manner that would be unexpected of an author widely labeled as ‘a man of his times’—and therefore a pro-imperial propagandist—in postcolonial literary criticism, he was critical of the anthropocentric ways of western civilization. Ranging from a Darwinian notion of the oneness of all living animals to a highly skeptical attitude toward the reckless exploitation of the resources of colonial lands and peoples, Haggard’s Weltanschauung included notions that were not only antithetical to imperialist discourses, but also ‘ahead of [their] times’ by more than a century. In this essay I elaborate on Haggard’s posthumanist eco-consciousness with reference to his fiction and conclude that a renewed understanding of Haggard’s literary and intellectual heritage would show how his works are still very much relevant and valuable in our time.